Endogenous CD317/Tetherin Limits Replication of HIV-1 and Murine Leukemia Virus in Rodent Cells and Is Resistant to Antagonists from Primate Viruses - Goffinet, Christine (American Society for Microbiology (ASM), 2010)
Human CD317 (BST-2/tetherin) is an intrinsic immunity factor that blocks the release of retroviruses, filoviruses, herpesviruses, and arenaviruses. It is unclear whether CD317 expressed endogenously in rodent cells has the capacity to interfere with the replication of the retroviral rodent pathogen murine leukemia virus (MLV) or, in the context of small-animal model development, contributes to the well-established late-phase restriction of human immunodeficiency virus type 1 (HIV-1). Here, we show that small interfering RNA (siRNA)-mediated knockdown of CD317 relieved a virion release restriction and markedly enhanced the egress of HIV-1, HIV-2, and simian immunodeficiency virus (SIV) in rat cells, including primary macrophages. Moreover, rodent CD317 potently inhibited MLV release, and siRNA-mediated depletion of CD317 in a mouse T-cell line resulted in the accelerated spread of MLV. Several virus-encoded antagonists have recently been reported to overcome the restriction imposed by human or monkey CD317, including HIV-1 Vpu, envelope glycoproteins of HIV-2 and Ebola virus, Kaposi's sarcoma-associated herpesvirus K5, and SIV Nef. In contrast, both rat and mouse CD317 showed a high degree of resistance to these viral antagonists. These data suggest that CD317 is a broadly acting and conserved mediator of innate control of retroviral infection and pathogenesis that restricts the release of retroviruses and lentiviruses in rodents. The high degree of resistance of the rodent CD317 restriction factors to antagonists from primate viruses has implications for HIV-1 small-animal model development and may guide the design of novel antiviral interventions.